Environmental and legal instruments of import control in colonial Nigeria, 1904-1954 (2020)
The colonisation of Nigeria by the British led to the merging of diverse ethnicities which occupied the area that later became Nigeria as the Europeans imposed administrative structures which included native court, native authorities, native treasuries and protectorates. Historians, political scientists, sociologists, economists and scholars of related disciplines have through their works, interrogated Nigeria’s colonial past. The Indirect Rule system, infrastructure, nationalism, currency circulation, systems of banking and education, and exploitation of resources are typical examples of Nigeria’s colonial experience. Similarly, scholars have made attempts at interrogating various aspects of the country’s colonial history. These include agricultural policies, export control policies, marketing boards, trade restrictions, politics of decolonisation, the politics of transfer of power, constitutional development, regionalism, nationalist movements, import control during and after World War II and the tariff system. These intellectual efforts have not beamed their searchlight on how the formulation of legal instruments which governed import control was aided by the nature of environment of certain regions in Nigeria. Against this backdrop, this paper interrogates the impact of the environment on Nigeria’s import control history in the colonial era. The paper concludes that the nature of Nigeria’s environment determined the efficacy of laws which governed import control administration in Nigeria.